Studi Komparatif Pengendalian Mutu Perencanaan Proyek Konstruksi Antara Metode Building Information Modeling (BIM) Dengan Metode Konvensional (Studi Kasus PT. Bita Enarcon Engineering) - saepudin, uu; sutrisna, dedi; firdaus, rifki (Jurnal Ilmiah Teknik Sipil, 2023)
Drawing planning is a crucial activity in a construction development. There is a new breakthrough in drawing planning,namely the Building Information Modeling (BIM) method which is known to be more effective and efficient than conventional methods. Every process of planning working drawings requires quality control so that the quality of the output produced is well maintained. Likewise with the Building Information Modeling (BIM) method, although it is superior to conventional methods, quality control efforts must still be carried out. This study aims to determine the qualitycontrol activities at PT. Bita Enarcon Engineering and compares the level of risk that occurs in the planning of workingdrawings between conventional methods and the Building Information Modeling (BIM) method. The method used in thisresearch is the distribution of questionnaires based on AS/NZS 4360:2004, namely Management System Standards. The results of the analysis show that the drawing planning quality control activities with conventional methods and Building Information Modeling (BIM) have the same process, namely self check, check print, and internal audit which contains inter discipline check. The resulting risk levels fall into two level categories, namely low and medium. The conceptual design has a score of 9.932 for the conventional method and 5.365 for the BIM method. The schematic design of the conventional method has a figure of 8.257 while for BIM it is 5.975. Followed by the development design, the conventionalmethod has a risk level of 8,559 and the BIM method is 6,536. And lastly for technical design, the conventional method has a risk level of 8.860 and the BIM method is included in the low category, namely 4.981. Although the risk level of the BIM method is smaller, it requires a higher cost compared to the conventional method.